Differential effects of support conditions on dynamic parameters - Fayyadh, M.M.; Abdul Razak, H.; Khaleel, O.R. (2011)
Investigation of the influence of the differences in the support conditions on the dynamic parameters are presented in this study. Bridge girders are usually supported by elastic bearings and suffer deterioration during the service life of the bridge. Early stages of deterioration of the elastic bearing occur with decrease in its stiffness. Advance stages of deterioration causes total damage of the elastic bearing, whereby the bridge girder will be supported directly on the structural element below it. The deterioration can occur on one or both sides of the supports. In order to study the effect of this phenomenon, experiments were conducted on a simply supported beam supported on elastic rubber pads with different stiffness as well as on steel supports. The undamaged support condition was simulated by using new rubber pads with stiffness of 10MN/m. The damage support conditions were represented by using old rubber pads with stiffness of 3 MN/m and using steel supports to simulate the case of total deterioration of the rubber bearing pads. Natural frequencies and mode shapes were obtained from modal testing and compared using of Modal Assurance Criteria MAC. The results showed a direct relationship between the support stiffness and the natural frequencies and mode shape. The first bending mode was most sensitive to the changes in support stiffness followed by Mode 2. It was also observed that the other modes had similar but lower sensitivity to the state of deterioartion of the supports.